All-in-Memory Brain-Inspired Computing Using FeFET Synapses - Thomann, Simon; Nguyen, Hong L. G.; Genssler, Paul R.; Amrouch, Hussam (Frontiers in Electronics, 2022)
The separation of computing units and memory in the computer architecture mandates energy-intensive data transfers creating the von Neumann bottleneck. This bottleneck is exposed at the application level by the steady growth of IoT and data-centric deep learning algorithms demanding extraordinary throughput. On the hardware level, analog Processing-in-Memory (PiM) schemes are used to build platforms that eliminate the compute-memory gap to overcome the von Neumann bottleneck. PiM can be efficiently implemented with ferroelectric transistors (FeFET), an emerging non-volatile memory technology. However, PiM and FeFET are heavily impacted by process variation, especially in sub 14nm technology nodes, reducing the reliability and thus inducing errors. Brain-inspired Hyperdimensional Computing (HDC) is robust against such errors. Further, it is able to learn from very little data cutting energy-intensive transfers. Hence, HDC, in combination with PiM, tackles the von Neumann bottleneck at both levels. Nevertheless, the analog nature of PiM schemes necessitates the conversion of results to digital, which is often not considered. Yet, the conversion introduces large overheads and diminishes the PiM efficiency. In this paper, we propose a PiM scheme performing computation and conversion all-in-analog at once, utilizing programmable FeFETs to build the comparator used for the conversion. Our experimental setup is first calibrated against Intel 14nm FinFET technology for both transistor electrical characteristics and variability. Then, a physics-based model of ferroelectric is included to realize the Fe-FinFETs. Using this setup, we analyze the circuit's susceptibility to process variation, derive a comprehensive error probability model, and inject it into the inference algorithm of HDC. The robustness of HDC against noise and errors is able to withstand the high error probabilities with a loss of merely 0.3% inference accuracy.